Profil bakteri non spesifik dalam lendir serviks sapi perah pada fase folikuler dan fase luteal - Nur, Maysarah Oktavia; Mulyati, Sri; Sardjito, Trilas; Chusniati, Sri; Tyasningsih, Wiwiek; Mafruchati, Maslichah (Universitas Airlangga, 2020)
This research was conducted to identify non-specific bacteria found in the cervical mucus of dairy cattle in the follicular and luteal phase. Twenty cervical mucus samples were collected from ten cows during their follicular phase and ten cows during their luteal phase. Sampling was carried out with the help of an artificial insemination gun and a plastic sheath, which were protected by a sheath cover. After insertion into cervix, the tip of the plastic sheath was cut and put into a tube prefilled with phosphate buffered saline. All samples were cultured in Blood Agar media and isolated in Eosin Methylene Blue Agar, Mac Conkey Agar, and Manitol Salt Agar. Gram staining was applied to distinguish gram-positive and gram-negative bacteria; and followed with the catalase, spore, motility, and biochemical tests to further identify bacteria. The bacteria identified were of the genus Enterobacter, Staphylococcus, Corynebacterium, Streptococcus, Escherichia, and Pasteurella. It could be concluded that non-specific bacteria of the same genus were identified in cervical mucus of dairy cows in their follicular and luteal phase, in a various of percentages.